The courses of objective physical activity and the association with sleepiness during a 2-week-on/2-week-off offshore shift rotation: an observational repeated-measures study - P. Ots; V. Riethmeister; J. Almansa; U. Bültmann; S. Brouwer (BMC, 2021)
Abstract Background Offshore workers are assumed to have poor health behaviours, but no studies have yet examined physical activity (PA) during a full offshore shift rotation period, including both work and at home periods. Furthermore, the relationship of PA with sleepiness, a prevalent safety hazard offshore, is not known. This study aimed to examine (1) the courses of objectively measured PA in offshore workers during pre-, offshore and post-offshore periods, and (2) the association between PA and self-reported sleepiness. Methods An observational repeated measures study was conducted among 36 offshore workers during a full 2-week on/2-week off offshore shift rotation. Objective PA was assessed using Daytime Activity Averages (DAA) from actigraph recordings. Sleepiness was assessed using next-morning Karolinska Sleepiness Scale (KSS) scores. The courses of PA over time were analysed with Linear Mixed Models (LMM). Parallel LMM were used to assess the longitudinal relationship between PA and sleepiness, both on a between-person and within-person level. Results The courses of PA were not significantly different between the pre-, offshore, and post-offshore periods. In addition, between-person trends of PA and sleepiness were not associated (p ranges between 0.08─0.99) and PA did not affect next-morning sleepiness on a within-person level (p = 0.15). Conclusions PA levels during the offshore working period were not different from PA levels at home. Furthermore, PA was not associated with next-morning sleepiness. Further research should focus on different levels of PA including its intensity level.